COMPARATIVE ANALYSIS OF COMPETITIVE STRATEGIES WITH BCG MATRIX APPROACH AT REGIONAL DEVELOPMENT BANKS - Satria Tirtayasa; Hasibuan, Lailan Safina; Afif (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aimed to determine the position of each regional development bank using bcg matrix approach and then analyze the comparison of competing strategies. Strategy analysis with bcg matrix, using market growth and relative market share as variables.  The method of analysis is quantitative descriptive. Banks that became the object of research are the top five regional development banks based on the total assets of the population of 27 regional development banks in Indonesia. To determine the position of regional development banks that became the object of research, bcg matrix analysis was performed. In this analysis, four regional development banks, namely bank jatim, bank jateng, bank dki and bank sumut were compared with bank bjb as the main competitor, while those compared to the bcg matrix analysis were certain financial data taken from the audited financial statements of each regional development bank from 2017 s.d. 2021. From this study, the following results were obtained: the position of bank jatim is in the question mark quadrant in 2017 - 2020 and the dogs quadrant in 2021. Bank jateng's position is in the question mark quadrant in 2017-2020 and the dogs quadrant in 2021. Bank dki's position is in the question mark quadrant in 2017-2019 and 2021 as well as the dogs quadrant in 2020. The position of bank sumut is consistently in the question mark quadrant in 2017-2021.